2019
DOI: 10.1155/2019/4901049
|View full text |Cite
|
Sign up to set email alerts
|

Automated Oxygen Delivery in Hospitalized Patients with Acute Respiratory Failure: A Pilot Study

Abstract: Background and Objectives. Despite its’ proven benefits, oxygen therapy may be complicated with potential adverse events such as hypoxemia or hyperoxia-driven hypercapnia. Automated oxygen delivery systems may aid in avoiding these complications. The scope of the present study is to test the efficacy and safety of a new automated oxygen delivery device. Methods. This study included 23 patients with acute respiratory failure (ARF) hospitalized in the Respiratory Medicine Department of the University Hospital of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The findings of our study are in line with previous studies testing the efficacy of closed-loop oxygen control in preterm infants and adults (16, [35][36][37][38][39][40][41][42][43][44] receiving HFNO for hypoxemia of various causes. In all those studies, closed-loop oxygen control outperformed healthcare workers performing manual oxygen titrations with respect to the percentage of time spent in target SpO 2 ranges and to the time spent in potentially dangerous SpO 2 zones .…”
Section: Discussionsupporting
confidence: 89%
“…The findings of our study are in line with previous studies testing the efficacy of closed-loop oxygen control in preterm infants and adults (16, [35][36][37][38][39][40][41][42][43][44] receiving HFNO for hypoxemia of various causes. In all those studies, closed-loop oxygen control outperformed healthcare workers performing manual oxygen titrations with respect to the percentage of time spent in target SpO 2 ranges and to the time spent in potentially dangerous SpO 2 zones .…”
Section: Discussionsupporting
confidence: 89%
“…The FiO2 subsequently should be increased only if the effect of pH is modest [83]. Automated oxygen delivery system may also have a potential role in patients with acute respiratory failure as it helps in controlled oxygen delivery [84]. Agusti et al [85] in a small randomized crossover study involving 18 hospitalised COPD patients with acute respiratory failure demonstrated improvement of oxygen tension by venturi masks and nasal prongs to the same extent, without any significant effect upon hypercarbia.…”
Section: Oxygen Therapy In Patients With Chronic Lung Diseasesmentioning
confidence: 99%
“…10 Recently, oxygen delivery systems using a closed-loop feedback system have been developed which enable continuous automated adjustment of a delivered oxygen concentration. [11][12][13][14][15] Studies of these devices have demonstrated patients spend a greater proportion of time with SpO 2 within target range compared with the standard practice of manual oxygen titration both in the emergency department (ED), 12 ward setting 13 and following abdominal and thoracic surgery. 11 To date, studies of automated oxygen titration in adults have involved conventional low-flow oxygen.…”
Section: Key Messagesmentioning
confidence: 99%